The influence of external disturbances on the aerodynamic performance of a wing in ground effect - Correia, Joao (Cranfield University, 2016)
Aerodynamic development of race cars is mostly performed in wind tunnels, where consistent and repeatable conditions can be found. This leads to race cars being designed to be very efficient in a uniform, low-turbulence flow. However, while running on the track the airflow passing over a car is frequently altered by the presence of other cars, ambient wind, or track conditions, which may lead to a change in aerodynamic performance. An experimental and computational study was set up in an attempt to understand the effects of real on-track performance-limiting factors such as roll, yaw and immersion in the wake of a leading car. The study was broken down into independent phases that allowed the collection of reference data, from a wing operating with and without roll and yaw in an undisturbed flow, wake data from a leading wake-generator representative of a monoposto car, and data from the wing operating in the wake of the leading vehicle. Results from the wake survey led to the identification of three main flow characteristics: low dynamic pressure in the wake, counter-rotating vortices that lead to local velocity components and high turbulence intensities in the wake. The negative influence of these flow characteristics was confirmed once the wing was immersed in the wake, as the wing suffered from a significant reduction in downforce throughout the tested ride height range. The results from the roll and yaw experiments showed that when operating in either condition an inverted wing in ground effect will experience the same downforce enhancement mechanisms as those present on a wing operating in an unrolled and unyawed condition. Although either roll or yaw showed reductions in the downforce generated by the wing, the roll results showed a small ride height range where it is possible to increase the generated downforce under certain flap and roll settings.